Perbandingan Hasil Belajar Biologi Siswa dengan Penerapan Strategi Belajar PQ4R dan Strategi Belajar Peta Konsep pada Materi Virus - Vonnisye Vonnisye (LPPM UKI Toraja, 2017)
This study aims to compared the biology learning results among students who used PQ4R (Preview,Question, Read, Reflect, Recite, Review) and students who used concept map learning strategy at the concept of Virus. The type of this study was quasi-experimental with Randomized Control Group Only Design. The learning strategy was the independent variable, which the first experimental class used PQ4R learning strategy and the second experimental class used concept map learning strategy. Learning results was the dependent variable which techniques of data collection was done by using learning result test. The learning result analyzed by used t-test (? = 5%). The result calculations showed signification figure of 0,006 (p< ?). It was concluded that there are difference of the learning result among student who used PQ4R (Preview, Question, Read, Reflect, Recite Review) learning strategy and students who used concept map learning strategy. The average value of students at the first class experiment who used PQ4R (Preview, Question, Read, Reflect, Recite Review) learning strategy was 69,74 and average value of the second class experiment who used Concept Mapp learning strategy was 73,20. It was concluded that concept mapp learning strategy better than PQ4R (Preview, Question, Read, Reflect, Recite Review) learning strategy.